2014
DOI: 10.1111/1467-8578.12057
|View full text |Cite
|
Sign up to set email alerts
|

The impact of video modelling on improving social skills in children with autism

Abstract: Children with autism often show a lack of the interactive social skills that would allow them to engage with others successfully. They therefore frequently need training to aid them in successful social interaction. Video modelling is a widely used instructional technique that has been applied to teach children with developmental disabilities such as autism, and has been shown to be effective in teaching a variety of skills. The aim of this study is to evaluate the impact of video modelling on social skills de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 23 publications
0
10
0
1
Order By: Relevance
“…A study by [15] shown that all types of models are effective, but some are more effective than others. On top of that, special education teachers are using video modelling as teaching material because it has been shown to be effective in teaching a variety of skills to special needs children specifically children with ASD [16]. c) Role-Playing Role-playing is an activity that allows special needs children to explore realistic situations and to teach them how to respond appropriately in the situations.…”
Section: Current Teaching Methods In Malaysiamentioning
confidence: 99%
“…A study by [15] shown that all types of models are effective, but some are more effective than others. On top of that, special education teachers are using video modelling as teaching material because it has been shown to be effective in teaching a variety of skills to special needs children specifically children with ASD [16]. c) Role-Playing Role-playing is an activity that allows special needs children to explore realistic situations and to teach them how to respond appropriately in the situations.…”
Section: Current Teaching Methods In Malaysiamentioning
confidence: 99%
“…Moreover, a study by Corbet et al [9] reported that by implementing peer-mediated theatrical treatment, social skills of students with ASD could be improved. Another study by Alzyoudi, Sartawi and Almuhiri [10] indicated that children with ASD could improve their social skills by modelling.…”
Section: Introductionmentioning
confidence: 99%
“…There was ample literature found which explored social development in differing settings (e.g. Alzyoudi et al, 2015;Koenig et al, 2010;Macnamara, 2015), however there was limited research of students educated exclusively in substantially separate settings. This research study explores a gap in the current literature.…”
Section: Summary Of Resultsmentioning
confidence: 99%
“…Another study that explored elementary aged individuals with autism spectrum disorder (ASD) was conducted by Alzyoudi et al (2015). This research article was a case study of five boys aged 5 to 7 years with a diagnosis of ASD.…”
Section: Teacher-mediated Interventionsmentioning
confidence: 99%
See 1 more Smart Citation